A local study on the incidence and risk factors of post-traumatic seizures among patients with traumatic brain injury - Chan kin, Hup (2009)
Post-traumatic seizures are a well-known and serious complication of traumatic brain injury. The incidence and risk factors vary among study populations. Very little data has been published concerning this in the population of Malaysia. The aim of this study was to ascertain the incidence and risk factors for the development of post-traumatic seizures among patients with traumatic brain injury in this part of the country. This was a prospective observational study, carried out in Hospital Universiti Sains Malaysia, Kubang Kerian Kelantan under the Department of Neurosciences. A total of 157 patients from any age group who were diagnosed with traumatic brain injury were enrolled from June 2007 to December 2007, then followed up for 12 months, until death or their first post-traumatic seizure. Patients were further divided into highrisk and low-risk groups and randomized to receive either phenytoin for 1 week or 1 year ( for the high-risk group ) and either phenytoin for 1 year or no phenytoin ( for the lowrisk group). Survival analysis using Kaplan-Meier curves and Cox proportional hazards regression were used. 26 out of 157 ( 16.6%) patients developed post-traumatic seizures. 11 of the 26 ( 42.3%) developed early post-traumatic seizures ( within 7 days ) of the trauma whereas the remaining 15 ( 57.7%) developed seizures between 8 days to 12 months after trauma. The mean time to develop late post-traumatic seizures was 9.4±3.2 months. The risk factors for developing early and late post-traumatic seizures were different. For early post-traumatic seizures, the risk factors were young age (p=0.021, 95% CI =0.806, 0.982) and intubated patients ( p=0.029, 95% Cl=1.194, 25.913 ). For late post-traumatic seizures, the significant risk factor was severe head injury with a Glasgow Coma Scale of 3-8 (p=0.036, 95% Cl=l.065, 6.464). Log-rank tests for phenytoin treatment in both high-risk and low-risk groups were insignificant (log-rank statistic of 0.31 with a p-value of 0.5784 for the high-risk group; log-rank statistic was 0.23 with a p-value of 0.6283 for the low-risk group). Incidence of post-traumatic seizures in the local population was 16.6%. Risk factors for early post-traumatic seizures were young age and intubated patients; whereas for late post-traumatic seizures, only severity of head injury was found to be signifi9ant. Phenytoin was not beneficial as prophylaxis against post-traumatic seizures.